UNIQUE EXTRA-LONG CHEMICALLY-DERIVED GRAPHITIC PYRAMIDAL RIBBONS - Chacón-Torres, Julio C.; Andrade-Guevara, Denise; García-Betancourt, María Luisa; Kröckel, Claudia (Acta Microscopica, 2024)
In this letter, unique extra-long chemically derived pyramidal graphitic ribbons (PGR) were individualized and deposited onto a SiO2 substrate via simple spin-coating. The length of the individualized PGRs was found to exceed the average length of graphene nanoribbons (GNRs) by hundreds of microns. The physicochemical individualization method resulted in the creation of a novel “graphene nanoribbon intercalation compound” (GNRIC), following a strict stoichiometric relation between the GNR powder and alkali metals. Our experiments were conducted with the use of Na and K as intercalants at NaC8, KC8, and KC24 concentrations. Furthermore, we exposed them to THF and discovered that the nanoribbon bundles obtained from CVD bottom-up bulk synthesis of GNRs can be exfoliated. The exfoliated nanoribbons (ex-GNRs) were analyzed using SEM, Raman spectroscopy, optical microscopy, and AFM, revealing the existence of ribbon-like pyramidal nanostructures that are larger than 100 µm. The morphology of these graphitic ribbons, brings a new starting point and immense potential to the development of graphene-based devices for optoelectronics and solar cells.
CRIS-Team Scopus Importer:2024-07-05
Keywords: Atomic force microscopy; Individualization; Intercalation compounds; Pyramidal graphitic ribbons; Raman spectroscopy